Exploration of Project and Module-based Teaching Method in Pharmaceutical Microbiology Laboratory Courses for Undergraduate Pharmacy Students - Chu, Weihua (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Pharmaceutical microbiology is an important applied branch of microbiology and it’s provided broad knowledge and understanding with regards to the principles, techniques and processes involved in pharmaceutical microbiological experiments. Objectives: To help students develop abilities related to laboratory techniques, data analysis, and systematic thought in biology, we have designed an exploratory program that employs project and the module-based teaching (PMBT) method. Materials and Methods: The PMBT experiments focus on the project of “Micro-organism limitation test of Shuanghuanglian oral preparation” and is divided into four modules. Results: The PMBT experiments guide students to experience an entire inquiry-based learning process by consistently conducting research projects, through which students gain an in-depth knowledge of the fundamentals of pharmaceutical microbial experiment skills. The PMBT experiments help student’s gain thorough understanding and reveal profound insights into pharmaceutical microbiology. It will essentially provide ample emphasis on the vivid coverage of the procedures involved in isolation of antagonistic micro-organism and improve student’s interest of study, the operational skills and scientific innovative abilities as well as enhance the quality of pharmaceutical microbiology education and teaching. Conducting the PMBT method in pharmaceutical microbiology experiments is beneficial to expanding students’ scientific vision, improving their operational capacity and their exploratory ability.
Keywords: Pharmaceutical microbiology; Innovative learning; Project and module-based experiment; Experimental and practice teaching reform; Research